Transmitter noise considerations in super‐Nyquist FMCW radar design. Issue 5 (1st March 2015) - Ash, M.; Brennan, P.V.
Abstract : A design consideration for super‐Nyquist frequency modulated continuous‐wave (FMCW) radar systems relating to transmitter to receiver noise leakage is introduced. Phase noise curves comparing the fundamental direct digital synthesisers frequency and its second super‐Nyquist image show a significant increase in relative noise level at all offsets from the carrier. This results in a reduced transmitter signal‐to‐noise ratio. It is shown with a simple example that this can lead to a significant degradation in receiver sensitivity if not managed properly. A design rule‐of‐thumb that can be used by radar designers to avoid or mitigate this problem is provided.